ACE and chitotriosidase as possible predictive biomarkers for activity of sarcoidosis in correlation with PET/CT findings - Sthepanovic, Mihailo; Sumarac, Zorica; Grubač, Draženka; Belic, Slobodan; Marić, Nikola; Djurdjevic, Natasa; Sumarac, Aleksandar; Jankovic, Jelena; Jovicic, Snezana (Journal of Medical Biochemistry, 2024)
Sarcoidosis is a granulomatous disease which can afflict virtually any tissue in human body, most commonly the mediastinal lymph nodes and lungs. Pathohistological confirmation is the gold standard in establishing a diagnosis; however, determining the activity of the disease requires multiple clinical, radiographic and laboratory procedures. PET/CT scan is considered the gold standard for determining the presence of active granuloma, but has several significant limitations (radioactive material, cost, overall access to device). ACE and chitotriosidase are biomarkers used for diagnosis of sarcoidosis, and could have a place in determining the activity of the disease, when compared with the results of PET/CT scan. We have compared the levels of ACE and chitotriosidase with the levels of SUVmax values in patients with sarcoidosis. SUVmax and chitotriosidase level were significantly correlated both at the baseline and after the follow-up period, regardless of gender, age, duration of disease and radiography stage, while SUVmax and ACE level were not. Chitotriosidase had also shown a significant predictive ability of the decrease of the activity of sarcoidosis represented as the decrease of SUVmax as the effect of therapy in comparison with ACE. In the absence of ideal biomarker for sarcoidosis (high sensitivity, specificity and stability), chitotriosidase can be used in determining the activity of disease, as it had shown a significant correlation to the gold standard- PET/CT scan.